Facets of Autophagy Based Unconventional Protein Secretion–The Road Less Traveled - Padmanabhan, Sreedevi; Manjithaya, Ravi (Frontiers in Molecular Biosciences, 2020)
Unconventional protein secretion (UCPS) of leaderless proteins bypasses the conventional Endoplasmic Reticulum (ER)-Golgi route. The proportion of UCPS in the secretome varies tremendously across eukaryotes. Interestingly, macroautophagy, an intracellular recycling process that is generally involved in cargo degradation, also participates in UCPS. This emerging field of secretory mode of autophagy is underexplored and has several unanswered questions regarding the composition of players, cargo and the mechanisms that drive it. As secretomes vary considerably across cell types and physiological conditions, the contribution of secretory autophagy in healthy and pathophysiological states remain to be elucidated. Recent studies have begun to shed light on this enigmatic process.